An "evasive neuter"? A study on neuter singular indefinite pronouns with human reference in seventeenth–nineteenth century literary German. (September 2022) - Fleischer, Jürg
Abstract : In the area of agreement with noun phrases displaying reference problems, "evasive forms" may be used to avoid problematic choices. When referring to people of more than one or unknown social gender, masculine or feminine forms might be inappropriate. An "evasive construction" solves this problem by turning to a form that is neither masculine nor feminine. A well-known example is "singular they " in English (e.g. anyone can do it if they try hard enough ). In literary New High German, neuter singular forms of indefinite pronouns could be used in similar contexts. This construction is largely obsolete in present-day Standard German but well attested until the nineteenth century and still current in some modern regional dialects. In this paper, the grammatical properties of this construction are discussed. It is shown that neuter gender is used for a specific semantic value, namely, to indicate more than one social gender simultaneously or to leave social gender explicitly open.